2020
DOI: 10.31234/osf.io/6ktuz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exposure to the Covid-19 pandemic and generosity

Abstract: The Covid-19 pandemic is having dramatic consequences across the world and has generated a public debate about how exposure to a pandemic environment affects social behavior: along with signs of increased solidarity such as people hand-making masks for others, we also observe selfish and antisocial behaviors such as harnessing of essential goods. This is a key question because prosocial behaviors are necessary to cope successfully with the pandemic, but the existing evidence provides no clear prediction regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 32 publications
3
40
0
1
Order By: Relevance
“…Interestingly, recent studies in adults have suggested that during the pandemic there is a shift towards pandemic-specific prosocial behaviors. For example, these studies have demonstrated that the pandemic makes individuals more likely to prioritize society's problems over their own, but less willing to give to non-COVID-19 related causes [37,38]. This interpretation also fits with our finding that Dictator Game giving is higher for COVID-19 related targets.…”
Section: Plos Onesupporting
confidence: 84%
See 1 more Smart Citation
“…Interestingly, recent studies in adults have suggested that during the pandemic there is a shift towards pandemic-specific prosocial behaviors. For example, these studies have demonstrated that the pandemic makes individuals more likely to prioritize society's problems over their own, but less willing to give to non-COVID-19 related causes [37,38]. This interpretation also fits with our finding that Dictator Game giving is higher for COVID-19 related targets.…”
Section: Plos Onesupporting
confidence: 84%
“…Second, it is noteworthy that attrition was larger for males than for females. There is currently no explanation for this difference, but it is worth noting that other pandemic studies have also shown higher participation of females compared to males [34,35,37,39]. To investigate the extent to which self-selection bias influenced our results, we examined whether adolescents who did not participate in the daily diary study differed from those who did, see S7 File.…”
Section: Strengths Limitations and Recommendations For Future Researchmentioning
confidence: 99%
“…Concerning other correlations with the CRT, previous work has also reported effects of gender ( Frederick, 2005 ; Campitelli and Gerrans, 2014 ; Thomson and Oppenheimer, 2016 ; Branas-Garza et al, 2020 ) using the classic three-item version, with male participants usually outperforming females. One reason given for this observation is that males have higher numeracy ( Baron et al, 2015 ), though Campitelli and Gerrans cite both numeracy and rational thinking ability, whereas others think the difference could be due to higher anxiety or lower self-assessment on numerical aptitude (e.g., Zhang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 97%
“…The results from the first-order correlation analysis and subsequent hierarchical regression modeling are relatively clear: demographic factors previously associated with health behavior ( Pack et al, 2001 ; Deeks et al, 2009 ), such as age (but not sex, see Branas-Garza et al, 2020 for a similar result regarding COVID-related donation behavior) as well as felt concern about the virus, explained a significant proportion of the variance on the DV, as did the RTI: older participants, respondents who were more concerned about the virus, and those self-reporting as less risk-taking in normal life, reported greater adherence to precautionary measures.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the same study found that prosociality measured two years before the pandemic predicts health behaviors during the pandemic. Another study found a significant decrease on generosity in an experiment was conducted six days during the early pandemic [ 48 ]. The authors explained such reduction suggesting that the Covid-19 threat may decreased generosity toward the “outgroup” or toward people not considered as part of the “ingroup”.…”
Section: Discussionmentioning
confidence: 99%